Applicability of existing performance evaluation tools and concepts to the Nigerian facilities management practice - Koleoso, Hikmot; Omirin, Modupe; Adewunmi, Yewande; Babawale, Gabriel (International Journal of Strategic Property Management, 2013)
There are noticeable gaps in aspects of Nigerian facilities management (FM) education and practice. Predicated by its relative infancy, one area where this gap is more apparent is in the measurement of performance. This paper is a systematic review of at least 22 performance measurement (PM) tools and concepts that are known and in use for assessment of performance of buildings / facilities and or performance of FM as a management process. Based on the literature, the research examined the essential features, strengths and weaknesses of each method generally and their specific applicability to the Nigerian environment, in view of her peculiarities as a developing nation. It also discusses the required attributes of a PM tool that will be applicable to FM in Nigeria. A major contribution of the study is the development of a table that presents a summary of the information on the tools or concepts at a glance. The paper is an extract from an ongoing PhD research; although it does not include details of the empirical survey, it nevertheless provides background work for a possible attempt at developing a PM tool that will be contextual and applicable to the measurement of building performance and effectiveness of facilities managers in the Nigerian FM practice and by extension, to most parts of the developing world. First Publish Online: 19 Dec 2013